Safety of Health Workers: A Key Priority in COVID-19 Pandemic - K.C., Bhakta Bahadur (Europasian Journal of Medical Sciences, 2021)
Although, the health workforce is one of the most significant building blocks of the health system, the preparation to ensure safety from COVID-19 remains inadequate across the world. Therefore, there is an increasingly growing number of health workers being infected from COVID-19 globally, making health workers the most vulnerable population to the pandemic. Most of the countries lack the safety equipment in place resulting in high exposure of health workers to this fatal SARS-COV2. Besides these, health workers' behaviour is also contributing infection to themselves. A high-level political commitment together with the investment in the health sectors to increase the supply of protective gears and capacity building of health workers is key to save and protect them from COVID-19 pandemic.